Massive Occurrence of the Harmful Benthic Dinoflagellate Ostreopsis cf. ovata in the Eastern Adriatic Sea - Živana Ninčević Gladan (Toxins, 2019)
In September 2015, a massive occurrence of the Ostreopsis species was recorded in central Adriatic Kaštela Bay. In order to taxonomically identify the Ostreopsis species responsible for this event and determine their toxin profile, cells collected in seawater and from benthic macroalgae were analyzed. Conservative taxonomic methods (light microscopy and SEM) and molecular methods (PCR-based assay) allowed the identification of the species Ostreopsis cf. ovata associated with Coolia monotis. The abundance of O. cf. ovata reached 2.9 × 104 cells L−1 in seawater, while on macroalgae, it was estimated to be up to 2.67 × 106 cells g−1 of macroalgae fresh weight and 14.4 × 106 cells g−1 of macroalgae dry weight. An indirect sandwich immunoenzymatic assay (ELISA) and liquid chromatography−high-resolution mass spectrometry (LC-HRMS) were used to determine the toxin profile. The ELISA assay revealed the presence of 5.6 pg palytoxin (PLTX) equivalents per O. cf. ovata cell. LC-HRMS was used for further characterization of the toxin profile, which showed that there were 6.3 pg of the sum of ovatoxins (OVTXs) and isobaric PLTX per O. cf. ovata cell, with a prevalence of OVTXs (6.2 pg cell−1), while the isobaric PLTX concentration was very low (0.1 pg cell−1). Among OVTXs, the highest concentration was recorded for OVTX-a (3.6 pg cell−1), followed by OVTX-b (1.3 pg cell−1), OVTX-d (1.1 pg cell−1), and OVTX-c (0.2 pg cell−1).